Soccer differences in order to explosive strength and rapidity among defenders, midfielders and forwards during COVID-19 - D'Apice, M.; Iona, T.; D'Isanto, T. (Journal of Human Sport & Exercise, 2021)
Problem statement. The aim of the study is to verify if the same protocol brings the same results towards the three roles of soccer, in terms of explosive power and speed, and if the COVID-19 affected the performance during the period September-December. Methods. Eighteen (n = 18) Italian élite soccer players, without goalkeepers, participated in this study (age 24.5 ± 5.9; body weight 75.2 ± 6.0; height 181.2 ± 7.1) from July to December, a period in which the whole team was infected by COVID-19. The players were monitored through two specific tests, CMJ and Speed test on 10 meters, detected in three different periods and in relation to three different playing positions: (D) defenders, (M) midfielders and (F) forwards. Soccer players have been trained following the same program training. A 3x3 Mixed-design analysis of variance was used to verify differences between the three roles and the results of the three measurements taken in July, September and December for each test. Results. The results is statistically significant (p < .05) for the within factor in the two tests, but there is no significant effect between groups (p > .05). Conclusion. In relation to the protocol used, we noticed that in terms of speed the forward role had the greatest improvement, while in terms of power in the lower limbs the role of the midfielder. Therefore, it is not possible to use the same training protocol for all roles, but to program your own personalized training plan based on the results of the match analysis and the performance model of each role.